1989
DOI: 10.1111/j.1467-6494.1989.tb00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Antecedents of Aggression and Passive‐Withdrawal in Early Elementary School

Abstract: Early childhood antecedents of elementary school aggression and passive-withdrawal were evaluated in a large longitudinal study (N = 191). With teacher ratings as outcome measures, a variety of predictor variables were selected from a comprehensive data base. Predictors were selected to represent several major factors: (a) a developmental history of insecure attachment and poor adjustment; (b) inadequate or hostile parental care; and (c) stressful or chaotic life circumstances. Support was found for the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
180
2
11

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(203 citation statements)
references
References 19 publications
10
180
2
11
Order By: Relevance
“…Dix's (1991) affective model of parenting suggests that negative emotions disruptive to the parent-child relationship result when parents have difficulty managing their own emotions, heavily favor self-oriented concerns over childoriented concerns, and lack adequate skills necessary for parenting. Supporting this Egeland and Farber (1984) demonstrated that high levels of maternal irritability, disinterest in parenting, and deficient caregiving skills were associated with avoidant attachments during infancy, an insecure classification that was related to later externalizing problems during preschool and school-age in the same sample (Erickson et al 1985;Renken et al 1989). Similar relations may be even more striking during the toddler period when noncompliance becomes more frequent and behavior is often difficult to control.…”
mentioning
confidence: 55%
“…Dix's (1991) affective model of parenting suggests that negative emotions disruptive to the parent-child relationship result when parents have difficulty managing their own emotions, heavily favor self-oriented concerns over childoriented concerns, and lack adequate skills necessary for parenting. Supporting this Egeland and Farber (1984) demonstrated that high levels of maternal irritability, disinterest in parenting, and deficient caregiving skills were associated with avoidant attachments during infancy, an insecure classification that was related to later externalizing problems during preschool and school-age in the same sample (Erickson et al 1985;Renken et al 1989). Similar relations may be even more striking during the toddler period when noncompliance becomes more frequent and behavior is often difficult to control.…”
mentioning
confidence: 55%
“…In the case of the latter, it is suggested that insecure "ambivalent" infants ("C" babies) are guided by a fear of rejection; consequently, in their extrafamilial peer relationships they are postulated to attempt to avoid rejection through passive, adultdependent behavior and withdrawal. This posited connection between C status (ambivalent attachment) and inhibited, dependent, withdrawn behaviors has been supported in several studies (e.g., Calkins & Fox 1992, Erickson et al 1985, Renken et al 1989, Shulman et al 1994.…”
Section: Parentingmentioning
confidence: 79%
“…Les attachements insécures mettent les enfants à risque de développer des problèmes comportementaux, quand ils sont combinés avec des situations de vie stressantes (décès d'un proche, divorce, changement de domicile de la famille,…) et avec des variations familiales (par exemple, naissances) (Erickson, Egeland, et Sroufe, 1985 ;Renken, Egeland, Marvinney et Sroufe, 1989). Cela est manifeste quand le caregiving et les facteurs contextuels négatifs sont permanents.…”
Section: Attachement Et Psychopathologieunclassified
“…Des histoires initiales d'attachement évitant ont pu être associées à l'agressivité dans la deuxième enfance (Renken et al, 1989) et à l'agressivité et la délinquance dans l'adolescence, spécialement chez les garçons. Le rôle de l'histoire précoce se reflète aussi dans l'étude de deux types de comportement antisocial des adolescents (Aguilar, Sroufe, Egeland, et al, 2000).…”
Section: Attachement Et Psychopathologieunclassified